The Impact of Deep Learning on Students' Learning Outcomes in Shalat Instruction - Junita Hasanah; Hilda Anjelita; Desva Usifa; Hanton Hanton; Afrizal Afrizal (International Journal of Islamic Teaching and Learning, 2026)
This study was motivated by the low achievement of elementary school students in learning shalat, highlighting the need for an effective instructional approach that can enhance students’ understanding, skills, and awareness during the learning process. The study aimed to examine the effect of the deep learning approach on students’ learning outcomes in shalat instruction within the Islamic Education subject. A quantitative research design was employed involving 42 fourth-grade students from two classes in a public elementary school in Indonesia. Data were collected through observation, pre-tests, post-tests, and documentation. The data were analyzed using tests of normality, homogeneity, and differences between group means. The findings revealed a statistically significant effect of the deep learning approach on students’ learning outcomes, with a two-tailed significance value below 0.05. The experimental group demonstrated a greater mean improvement (25.95) than the control group (12.14). These findings indicate that the implementation of the deep learning approach in Islamic Education significantly enhances students’ academic achievement in shalat learning.